2015
DOI: 10.1111/edt.12198
|View full text |Cite
|
Sign up to set email alerts
|

What do dental students know about trauma?

Abstract: Lectures are effective at improving the knowledge and retention of knowledge of dental undergraduate students in dental trauma. However, retention of the knowledge is time limited suggesting that education should be repeated after a certain period of time to ensure that a high level of knowledge is maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 11 publications
10
47
0
1
Order By: Relevance
“…On the other hand, a shorter period of 3 months was preferred in the present investigation to provide a varying data to educators in terms of the repetition of knowledge. As this was a study on a voluntary basis, nearly 50% of the class accepted to participate, similar to some previous studies [4]. A lower number of participants were males which was compatible with the relatively lower number of male students enrolled in class.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…On the other hand, a shorter period of 3 months was preferred in the present investigation to provide a varying data to educators in terms of the repetition of knowledge. As this was a study on a voluntary basis, nearly 50% of the class accepted to participate, similar to some previous studies [4]. A lower number of participants were males which was compatible with the relatively lower number of male students enrolled in class.…”
Section: Discussionsupporting
confidence: 80%
“…A study performed in the UK revealed that dental trauma is the topic in which students feel the least self-confidence [30]. In the UK and Japan, students' knowledge has been found to be inadequate when dental trauma is concerned [4,31]. The results of the present study correlate with these findings as there is a necessity for students close to graduation to develop their knowledge in the management of dental trauma.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations